Molecular mechanism study of EGFR allosteric inhibitors using molecular dynamics simulations and free energy calculations. Issue 13 (21st July 2022) - Wu, Xiaoyun; Guo, Qian; Li, Qinlan; Wan, Shanhe; Li, Zhonghuang; Zhang, Jiajie
ABTRACT: The epidermal growth factor receptor (EGFR) kinase inhibitors Gefitinib, Erlotinib, Afatinib and Osimertinib have been approved for the treatments of non-small cell lung cancer patients harboring sensitive EGFR mutations, but resistance arises rapidly. To date all approved EGFR inhibitors are ATP-competitive inhibitors, highlighting the need for therapeutic agents with alternative mechanisms of action. Allosteric kinase inhibitors offer a promising new therapeutic strategy to ATP-competitive inhibitors. The mutant-selective allosteric EGFR inhibitors EAI045 exhibited higher potency for EGFR L858R&T790M compared to WT, which was also effective in EGFR-mutant models including those harboring the C797S mutation. However, it was not effective as a single-agent inhibitor, and require the co-administration of the anti-EGFR antibody Cetuximab. Further efforts produced a more potent analog JBJ-04-125-02, which can inhibit cell proliferation as a single-agent inhibitor. In the present study, molecular dynamics simulations and free energy calculations were performed and revealed the detailed inhibitory mechanism of JBJ-04-125-02 as more potent EGFR inhibitor. Moreover, the energy difference between HOMO and LUMO calculated by DFT implied the higher interaction of JBJ-04-125-02 than EAI045 in the active site of the EGFR. The identified key features obtained from the molecular modeling enabled us to design novel EGFR allosteric inhibitors. Communicated by Ramaswamy H. Sarma